Fullerene-water nanofluid confined in graphene nanochannel - Zhen Liu; Zhong-Qiang Zhang (AIP Advances, 2017)
The flow behaviors and boundary slip of the fullerene-water nanofluids (NFs) confined in graphene nanochannels are first investigated by using classical molecular dynamics simulations. The influences of the shear rate in Couette model, the driving force in Poiseuille model, the volume fraction, and the charge magnitude on the motion behaviors and the boundary slip are explored with considering the dynamics and the accumulation of the fullerene within the NFs. The results show that the boundary slip velocity increases almost linearly with the shear rate below a threshold of the shear rate while it increases sharply above the threshold. The relatively large driving force in Poiseuille model and the large shear rate in Couette model can reduce the accumulation of the fullerenes. The increase in the volume fraction of the fullerene in NFs can enhance the shear viscosity, and interestingly, it can increase the boundary slip velocity of the NFs in graphene channels. As the charge magnitude of the graphene channel increases, the boundary slip of fullerene NFs first increases to a threshold and then decreases slightly. The findings may be helpful to the design and fabrication of the low dimensional carbon materials-based nano-apparatus.